PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN MASYARAKAT TERHADAP KEPUASAN DALAM PEMBUATAN E-KTP DI KECAMATAN COBLONG KOTA BANDUNG - Herliani Putri Ratnaningsih; Yogi Suprayogi Sugandi; Indra Aldila Wiradiputra (Halu Oleo University, 2023)
This study aims to determine the effect of the role of service quality and trust on community satisfaction in making e-KTPs in the Coblong sub-district in the city of Bandung. The samples taken in this study were 98 people using the incidental technique, namely determining the sample based on chance that met the criteria. Data analysis used multiple regression with the help of the SPSS 23 application for windows. The results of this study show that service quality and trust have a significant influence on people's satisfaction in making e-KTPs. The result of the coefficient of determination is 78.3% indicating that the two variables (service quality and trust) have a strong relationship in increasing community satisfaction. This research also has managerial implications, especially for service providers to provide the best service and build an image so that community satisfaction increases.